The Economic Well-Being of Nonresident Fathers and Custodial Mothers Revisited: The Role of Paternal Childcare - Christina Boll; Simone Schüller (Journal of Family and Economic Issues, 2022)
Based on panel data from the German Socio-Economic Panel (SOEP) for the years 1998 to 2018, we investigate the association between paternal childcare and parental economic well-being after separation in Germany. Referring to the post-separation year, we explore a sample of 176 separated couples with resident mothers and nonresident fathers, where fathers differ in their childcare involvement during weekdays. We propose equivalized annual net household income after exchange of alimony and child maintenance payments among the ex-partners as a novel indicator of parental economic well-being. Our study reveals the importance of considering both paid and received alimony, and child maintenance payments in analyzing post-separation economic well-being. Fathers' childcare engagement during weekdays is not significantly associated with maternal post-separation income. Resident mothers take up the major or even full childcare burden. On the other hand, fathers with non-zero childcare hours manage to combine some paternal engagement with intensified employment. Mothers, however, fail to gain substantial ground on the labor market, which is unlikely to be due to differences in human capital, but rather due to persistently high maternal childcare involvement. We conclude that neither high levels of own resources, nor receiving help with childcare during the week shield resident mothers from economic deterioration after separation.
Keywords: J12; J13; J16; J22; 300; Separation; Childcare; Household income; Socio-Economic Panel Study; Germany